Art, artifice and androgyny: Roxy Music's dandy modernism. Issue 2 (1st April 2015) - Hackett, Jon
This article considers glam rock's rejection of the humdrum, spontaneity and the 'natural', and its embrace of costuming, camp and artificiality. With particular reference to Roxy Music, it will examine the band's iconography, fashion and contexts during glam's golden years – 1972 to 1974 – as well as the implications of glam style for gender and sexuality in popular music. Though some of glam's exponents were undoubtedly much more traditional in their performance of gender identities, we can read bands like Roxy Music, within certain limits, as 'queering' their more meat-and-potatoes predecessors and providing an important source of identification for later pop music gender and style dissidents. The fashion and music scenes in which Roxy Music emerged are inseparable from the milieux of experimentation and innovation associated with British art and fashion schools in the 1960s onwards. To this extent, the band exemplifies the vital pathway of art school students into popular music outlined by Simon Frith and Howard Horne in Art into Pop. Through Keir Keightley's conception of romantic and modernist authenticity in popular music and Joanne Entwhistle's genealogy of the romantic and the dandy in fashion, we will explore how glam traces a line from the dandy via New Edwardian fashion, in which questions of gender and artifice are in a process of perpetual renegotiation.